2023
DOI: 10.3389/fphar.2023.1115117
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile, in vitro antimicrobial and in vivo diuretic effects of endemic wild thyme Thymus comosus Heuff ex. Griseb. (Lamiaceae) from Romania

Abstract: Thymus comosus Heuff ex. Griseb. (Lamiaceae) is a wild thyme species endemic for Romanian Carpathian areas, frequently collected as substitute for collective herbal product Serpylli herba, cited as antibacterial and diuretic remedy in traditional medicine. The present study aimed to evaluate the in vivo diuretic effect and in vitro antimicrobial properties of three herbal preparations (infusion—TCI, tincture—TCT and an hydroethanolic extract prepared through an optimized ultrasound-assisted method—OpTC) obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Nevertheless, this is the first report on the antibacterial activity of the depsides clinopodic acids I and O, as well as melitric acid A, whereas for rosmarinic acid, the literature reports are contradictory. Several extracts from plants of the Lamiaceae family containing rosmarinic acid, such as S. hortensis , are reported to be active [ 62 , 63 ]. On the contrary, rosmarinic acid alone does not show any antibacterial activity against Staphylococcus aureus [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this is the first report on the antibacterial activity of the depsides clinopodic acids I and O, as well as melitric acid A, whereas for rosmarinic acid, the literature reports are contradictory. Several extracts from plants of the Lamiaceae family containing rosmarinic acid, such as S. hortensis , are reported to be active [ 62 , 63 ]. On the contrary, rosmarinic acid alone does not show any antibacterial activity against Staphylococcus aureus [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils from Lamiaceae representatives have previously been studied for their antibacterial potential. It has been demonstrated that they can, independently or in combination with existing antibiotic drugs, inhibit bacterial cell growth, diminish the virulence of highly resistant strains such as MRSA (Methicillin-resistant Staphylococcus aureus ), and both hinder the formation and induce the degradation of pre-existing biofilms in specific bacteria [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, to this day, there is a limited amount of research available on the antibacterial mechanisms of extracts derived from these plants.…”
Section: Introductionmentioning
confidence: 99%